2013
DOI: 10.1158/2326-6066.cir-13-0043-t
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Inhibits CD8 T-cell Activation and Control of Tumor Progression

Abstract: CD8 T lymphocytes are able to eliminate nascent tumor cells through a process referred to as immune surveillance. However, multiple inhibitory mechanisms within the tumor microenvironment have been described that impede tumor rejection by CD8 T cells, including increased signaling by inhibitory receptors. Lysophosphatidic acid (LPA) is a bioactive lysophospholipid that has been shown repeatedly to promote diverse cellular processes benefiting tumorigenesis. Accordingly, the increased expression of LPA and LPA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 59 publications
(71 reference statements)
6
97
0
Order By: Relevance
“…While attention on LPA has focused on its aberrant production by diverse cancer cell types and its ability to promote tumorigenesis (18, 21, 22), our data suggest that certain malignancies might exploit LPA production not only to promote tumorigenesis but also as a mechanism to inhibit adaptive immune responses (53). In the future it will be important to consider that the pathological or therapeutic settings that alter LPA levels or LPA receptor signaling will also likely modulate adaptive humoral immunity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…While attention on LPA has focused on its aberrant production by diverse cancer cell types and its ability to promote tumorigenesis (18, 21, 22), our data suggest that certain malignancies might exploit LPA production not only to promote tumorigenesis but also as a mechanism to inhibit adaptive immune responses (53). In the future it will be important to consider that the pathological or therapeutic settings that alter LPA levels or LPA receptor signaling will also likely modulate adaptive humoral immunity.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, we have demonstrated that LPA signaling via the LPA 5 receptor expressed by tumor-specific CD8 T cells suppresses tumor immunity (53). Our findings here show that physiological and pathophysiological concentrations of LPA act on the LPA 5 receptor to suppress BCR-mediated calcium release from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pieces of evidence point to the involvement of lysophosphatidic acid in the signaling cascades that facilitate the initiation, development, and dissemination of ovarian cancer. Moreover, lysophosphatidic acid induces the formation of inflammatory cytokines, which favor the survival of malignant cells and predetermine their more aggressive behavior (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…LPA receptor expression and function on CD8+ T cells has not yet been widely studied. In a recent study Oda et al found that mouse CD8+ T cells express LPA2, 5, and 6 and that LPA5 suppresses CD8+ T cell receptor activation, signaling, and tumor immunity [56]. The CD4+ T cell studies were performed before the identification of the P2Y family of receptors (LPA4–6) and the expression of all of the LPA receptors over the course of T cell activation has not been rigorously examined.…”
Section: Discussionmentioning
confidence: 99%